SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN HANDPHONE DENGAN MENGGUNAKAN METODE WEIGHT PRODUCT - Muslimah Katoningati; Adhika Pramita Widyassari (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2021)
Mobile as a telecommunication equipment which is the main requirement nowadays, is equipped with many features that every mobile phone has. The large number of types of mobile phones makes consumers have to be smart in choosing cellphones that can be used every day. Not understanding the advantages and disadvantages of improperly chosen mobile phones can cause harm to consumers based on the user's interest level. In this study, a calculation analysis will be carried out with some alternative data for mobile phones based on predetermined criteria using the weighted product method, which can solve the problem by multiplying to connect the rating attribute with the weight attribute concerned. It is expected that from the concept of this calculation analysis can become knowledge about the weighted product method in the selection of recommended cellphones, as a basis for an overview for developing the implementation of the weighted product method into further research.